ANALISIS KOMPARATIF TEORI EVALUASI PENDIDIKAN: MODEL TYLER, SCRIVEN, STUFFLEBEAM (CIPP), DAN STAKE - Andrini Rosa Putri Siregar; Atikah Rahmah Nasution; Mariam Nasution (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Evaluation is a strategic component in the education system that serves as a basis for decision-making to improve the quality of learning and educational programs. Various evaluation models have been developed to address diverse evaluation needs according to the objectives, context, and characteristics of the program being assessed. This article aims to comprehensively analyze the Tyler, Scriven, Stufflebeam (CIPP), and Stake evaluation models and identify their strengths, limitations, and relevance in modern educational practice. The research uses a literature review method with a descriptive-analytical approach through a review of various relevant scientific sources. The results of the study indicate that the Tyler Model emphasizes the achievement of educational objectives as an indicator of program success. The Scriven Model develops formative and summative evaluations as well as goal-free evaluations that enable a broader identification of program impacts. The CIPP Model offers a comprehensive evaluation approach through the evaluation of context, input, process, and product, thus supporting sustainable decision-making. Meanwhile, the Stake Model emphasizes evaluation that is responsive to the needs of stakeholders and real-world conditions. The findings indicate that no evaluation model is completely superior to the others because each has a different focus, strengths, and limitations. Therefore, the selection of an evaluation model needs to be adjusted to the objectives, characteristics of the program, and the information needs to be obtained.